An expanding universe of noncoding RNAs between the poles of basic science and clinical investigations. (March 2016) - Weil, Patrick P; Hensel, Kai O; Weber, David; Postberg, Jan
The Keystone Symposium 'MicroRNAs and Noncoding RNAs in Cancer', Keystone, CO, USA, 7–12 June 2015: Since the discovery of RNAi, great efforts have been undertaken to unleash the potential biomedical applicability of small noncoding RNAs, mainly miRNAs, involving their use as biomarkers for personalized diagnostics or their usability as active agents or therapy targets. The research's focus on the noncoding RNA world is now slowly moving from a phase of basic discoveries into a new phase, where every single molecule out of many hundreds of cataloged noncoding RNAs becomes dissected in order to investigate these molecules' biomedical relevance. In addition, RNA classes neglected before, such as long noncoding RNAs or circular RNAs attract more attention. Numerous timely results and hypotheses were presented at the 2015 Keystone Symposium 'MicroRNAs and Noncoding RNAs in Cancer'.